Immigrant Protest Politics, Aesthetics, and Everyday Dissent - Marciniak, Katarzyna; Tyler, Imogen (SUNY Press Open Access; SUNY series, Praxis: Theory in Action, 2014)
The last decade has witnessed a global explosion of immigrant protests, political mobilizations by irregular migrants and pro-migrant activists. This volume considers the implications of these struggles for critical understandings of citizenship and borders. Scholars, visual and performance artists, and activists explore the ways in which political activism, art, and popular culture can work to challenge the multiple forms of discrimination and injustice faced by "illegal" and displaced peoples. They focus on a wide range of topics, including desire and neo-colonial violence in film, visibility and representation, pedagogical function of protest, and the role of the arts and artists in the explosion of political protests that challenge the precarious nature of migrant life in the Global North. They also examine shifting practices of boundary making and boundary taking, changing meanings and lived experiences of citizenship, arguing for a noborder politics enacted through a "noborder scholarship. "